Peran Pendidikan Pesantren dalam Membentuk Generasi Muda yang Berkarakter Integritas - Dedi Ardiansyah; Iswahyudi (INTEGRATIA: Journal of Education, Human Development, and Community Engagement, 2023)
The young generation with integrity has an important role in efforts to achieve progress and excellence for a nation, because the progress of a nation's civilization is very dependent on the condition of its youth. This research examines the ethical and moral problems that are increasingly declining among the younger generation and reveals the important role that Islamic boarding schools must play in overcoming this problem. The problems identified involve a decline in moral values, an increase in destructive behavior, and a low awareness of integrity in various aspects of the lives of the younger generation, as based on KPAI data in 2022, there were 226 cases of physical and psychological violence including bullying committed by Indonesian students. This research uses a critical descriptive method, providing a description of Islamic boarding school education and exploring an in-depth understanding of the values, principles and educational methodology promoted by Islamic boarding schools. The research results show that Islamic boarding school education provides a strong foundation for the younger generation to develop the character of integrity, because the education is based on the Al-Qur'an and Hadith. An in- depth understanding of Islamic boarding school education emphasizes the urgency of the role of these institutions in forming a young generation with integrity. This research underlines the urgency of Islamic boarding school education as the main solution in overcoming moral and ethical problems among the younger generation. Therefore, this research emphasizes that Islamic boarding school education must receive support and receive more serious attention as a strategic effort in forming a young generation with integrity, to create a superior future for the nation.